Payments remain fundamental for banks and central banks - Ralf Pauli (Bank of Finland, 2000)
Is commercial banking in the traditional sense obsolete?Are we in fact witnessing the emergence of a fundamentally new era of finance and payments intermediation?These questions are raised in this paper.Instead of a formal analysis, an attempt is made here to approach these questions from a historical perspective and a practitioner's standpoint.Which factors have in the course of time shaped the role of commercial banks and are present trends in the market eroding the foundation of traditional commercial bank functions to the extent that we are actually entering upon something that is new in a fundamental way. Of course, we will not get definitive answers.The conclusion arrived at in the paper is that banks will remain important intermediators of financing and payments, and that these functions will constitute the core of banking also in the foreseeable future. This however does not exclude structural changes in the banking sector as a whole and in the activities of individual banks.On the contrary, these are essential to the survival of banks. The paper analyses prospects for new media of exchange replacing deposit money.It is concluded that, as regards asset transfers in the capital market becoming a dominant medium of exchange (in the spirit of the New Monetary Economics), there are serious impediments. Payment flows have increased sharply at the same time as the whole banking sector has been making the adjustment to a more competitive situation.This has accentuated the role of the central bank as a payments service provider to the banks and particularly as an overseer of payment systems.The central bank's role as payment systems overseer is likely to receive even greater emphasis in the future.The central bank's oversight mandate requires further specification as regards the payment systems to be overseen and how oversight relates to banking supervision. Our analysis demonstrates also that current trends in the market are not weakening but rather are strengthening the traditional interrelationship between banks and the central bank in the field of payments.The roles of the banks and the central bank still need fine tuning.It is concluded that payment systems can best serve the rest of the economy if the prime responsibility to develop the systems is left to the private sector, while the central bank has a recognized position as a public policy entity that will do what is necessary to achieve a sufficient level of safety and efficiency.
URN:NBN:fi:bof-20140807524
Keywords: 330; payments; oversight; medium of exchange; bank; central bank